Role of nutritional therapy in the post-COVID syndrome rehabilitation process: a case report - Araújo, Cintia Galeno; Danziato-Neto, Milton Alves; Lima, Rebecca Emanuelle Freitas; Melo, Ângela Nirlene Monteiro Vieira; Santos, Ana Angélica Queiroz Assunção (Brazilian Journal of Case Reports, 2023)
The COVID-19 pandemic originated in Wuhan, China, and quickly became a global concern. Risk factors for complications, apart from age, are closely related to nutrition. In hospitalized patients, extended stays can lead to malnutrition and sarcopenia, highlighting nutrition's pivotal role in managing and alleviating symptoms. This study explores the efficacy of nutritional therapy for post-COVID patients within the Home Care Program framework. Following hospital discharge, the patient was enrolled in the Home Care Program and showed symptoms such as post-COVID-19 condition, significant pressure injury, low weight, and muscular atrophy. A multi-professional developed a therapeutic plan with a focus on nutrition. Within 70 days, a 58-year-old male patient, supported by nutritional supplementation including arginine, proline, and vital vitamins and minerals, exhibited considerable health improvements. These included a progression of nutritional status to eutrophy, a weight gain of 6 kg since the beginning of the intervention, and a 15.7% increase in MUAC adequacy. The nutritional intervention also effectively tackled issues like constipation. These enhancements enabled the patient to respond better to physical therapy, reclaiming significant daily activity autonomy. Comprehensive nutritional therapy is instrumental for recovering post-COVID-19 patients, accentuating the importance of personalized care in ensuring patient well-being and autonomy.